Patterns and Practices in the Use of Endodontic Materials: Insights from Romanian Dental Practices - Diana Marian; Ramona Amina Popovici; Iustin Olariu; Dana Emanuela Pitic (Cot); Maria-Monica Marta; Ioana Veja (Ilyes) (Applied Sciences)
The success of endodontic treatment depends on the correct use of materials during the cleaning and filling of the root canal system. The field of endodontics is constantly evolving with the introduction of new procedures and materials. Despite the continuous development of a wide range of chemical solutions and the introduction of new materials in endodontics, driven by the advances in state-of-the-art technologies, there is still a lack of data on how these advances are adapted to the daily practice of Romanian dentists in this field. The aim of this cross-sectional questionnaire-based study was the evaluation of current trends in endodontic practice, focusing on the materials used by dentists throughout Romania, performed by a number of dentists who graduated from universities in the Northern, Southern, Eastern, Western, and Central zones of Romania. The questions were about the irrigants used, the interim medication, the type of sealant, the filling technique, and the number of endodontic treatment sessions. The majority of participants in the research were general practitioners and endodontists, with some dentists of different specialties performing endodontic treatments in their practices. Statistical analyses were performed using DATAtab version 2024 software. The results obtained from this study provide a valuable resource and database for researchers to access a wide range of information and an apparent trend towards high-performance endodontic materials used in Romania.